2012
DOI: 10.1021/jz300562v
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Monte Carlo Study of Ambipolar Lithium Ion and Electron–Polaron Diffusion into Nanostructured TiO2

Abstract: Nanostructured titania (TiO 2 ) polymorphs have proved to be promising electrode materials for next-generation lithium ion batteries. However, there is still a lack of understanding of the fundamental microscopic processes that control charge transport in these materials. Here, we present microscopic simulations of the collective dynamics of lithium ion (Li + ) and chargecompensating electron−polarons (e − ) in rutile TiO 2 nanoparticles in contact with an idealized conductive matrix and electrolyte. Kinetic M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…28 Even before this complex was observed by EPR and electron nuclear double resonance (ENDOR), 29 its effect on the mobility of Li + was considered theoretically. 12,30 To study lithium-ion dynamics in rutile, a technique sensitive to the local environment of Li + is desirable. Nuclear magnetic resonance (NMR) is a sensitive microscopic probe of matter with a well-developed toolkit for studying ionic mobility in solids.…”
Section: Introductionmentioning
confidence: 99%
“…28 Even before this complex was observed by EPR and electron nuclear double resonance (ENDOR), 29 its effect on the mobility of Li + was considered theoretically. 12,30 To study lithium-ion dynamics in rutile, a technique sensitive to the local environment of Li + is desirable. Nuclear magnetic resonance (NMR) is a sensitive microscopic probe of matter with a well-developed toolkit for studying ionic mobility in solids.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocrystalline oxides, encompassing both porous powders and dense ceramic materials, are a ubiquitous form of technological material. However, TiO 2 is perhaps exceptional in the incredibly wide range of applications it finds, including photocatalysts for self‐cleaning glass and water splitting, dye‐sensitized solar cells (DSSCs) for solar energy generation, Li‐ion battery materials for energy storage and resistive switching memories for low power and non‐volatile data storage . Key to the performance of these varied applications is the transport of electrons which may be introduced by optical excitation, electrical injection or doping.…”
mentioning
confidence: 99%
“…To fully assess the effect of the grain boundary on mobility we simulate the correlated electron transport of a flux of electrons across a bicrystal using a KMC approach similar to that used in previous studies of electron transport in nanocrystalline TiO 2 and hematite . The rate of electron hopping between sites is described using the formalism of Marcus, Emin, Holstein, Austin and Mott which gives the electron transfer rate in terms of the diabatic activation energies calculated above and the electronic coupling matrix elements H ab (see Supporting Information for details).…”
mentioning
confidence: 99%
“…In theoretical models that include the effects of these ions, they are usually considered as surface-adsorbates. On the other hand, from battery research, we now know that insertion of large amounts of metal atoms into TiO 2 is possible [16,[46][47][48]. It has also been reported that anatase TiO 2 anodes in DSSC can undergo a phase transition to the B phase [49].…”
Section: Introductionmentioning
confidence: 99%